Strengthening the knowledge–policy interface through co-production of a climate adaptation plan: leveraging opportunities in Bergrivier Municipality, South Africa. (October 2016) - Ziervogel, Gina; Archer van Garderen, Emma; Price, Penny
Despite the growth of adaptation plans and action by municipalities, there are limited examples of opportunities for effectively mainstreaming climate adaptation into policy and practice in local government. This paper uses the experiment of co-producing an adaptation plan for a small municipality in the Western Cape Province, South Africa, to illustrate how opportunities were leveraged. The findings suggest that a shift from strengthening the science–policy interface to the knowledge–policy interface might be more appropriate in the context of adaptation planning that requires an understanding of the local context as well as of global science. In order to align adaptation plans with developmental priorities and to secure support from actors at multiple levels, the integration of multiple knowledge forms, including climate science, should be prioritized. Such a task could be strengthened if co-production is prioritized. Building on these opportunities is critical to scaling up adaptation in local government and building on its transformative potential.